Single-cell genomics based on Raman sorting reveals novel carotenoid-containing bacteria in the Red Sea. - Song, Y; Kaster, A; Vollmers, J; Song, Y; Davison, P; Frentrup, M; Preston, G; Thompson, I; Murrell, J; Yin, H; Hunter, C; Huang, W (Wiley, 2016)
Cell sorting coupled with single-cell genomics is a powerful tool to circumvent cultivation of microorganisms and reveal microbial ‘dark matter’. Single-cell Raman spectra (SCRSs) are label-free biochemical ‘fingerprints’ of individual cells, which can link the sorted cells to their phenotypic information and ecological functions. We employed a novel Raman-activated cell ejection (RACE) approach to sort single bacterial cells from a water sample in the Red Sea based on SCRS. Carotenoids are highly diverse pigments and play an important role in phototrophic bacteria, giving strong and distinctive Raman spectra. Here, we showed that individual carotenoid-containing cells from a Red Sea sample were isolated based on the characteristic SCRS. RACE-based single-cell genomics revealed putative novel functional genes related to carotenoid and isoprenoid biosynthesis, as well as previously unknown phototrophic microorganisms including an unculturable Cyanobacteriaspp. The potential of Raman sorting coupled to single-cell genomics has been demonstrated.